A practitioner's guide to emphasizing choice-making opportunities in behavioral services provided to individuals with intellectual and developmental disabilities. (2nd January 2023) - Rajaraman, Adithyan; Austin, Jennifer L.; Gover, Holly C.
Abstract : Promoting choice is a defining value guiding Positive Behavior Support (PBS) models for serving individuals with intellectual and/or developmental disabilities (IDD). The ability to make independent choices is of paramount importance to self-advocacy and self-determination. Promoting choice is also an essential commitment of trauma-informed care (TIC) in the provision of services to vulnerable individuals, as trauma often involves experiences in which an individual has no control over aversive events that occur, and choice-making opportunities can empower traumatized individuals to regain control over the environments they routinely encounter. However, incorporating meaningful choice making into behavioral programming is often more difficult than it seems. We synthesize the relevant, contemporary literature to provide professionals with actionable suggestions for incorporating choice making into everyday behavioral services. After summarizing the importance of promoting choice into behavioral services based on the values that define both PBS and TIC frameworks, we (a) offer a behavior-analytic interpretation of the skill of making choices, (b) synthesize key literature on how to teach choice making skills, (c) provide recommendations for the situations within one's care in which choice-making opportunities may be most beneficial, and (d) discuss some of the barriers and potential solutions to incorporating choice-making opportunities for individuals with IDD.